Pharmaco‐parasitological evaluation of the ricobendazole plus levamisole nematodicidal combination in cattle. Issue 1 (10th July 2017) - Canton, C.; Ceballos, L.; Domínguez, M. P.; Moreno, L.; Fiel, C.; Bernat, G.; Farías, C.; Lanusse, C.; Alvarez, L.
Abstract : The goals of the current study were to evaluate the potential pharmacokinetic (PK) interactions and the clinical efficacy occurring after the subcutaneous (s.c.) administration of ricobendazole (RBZ) and levamisole (LEV) given both separately and co‐administered to calves naturally infected with susceptible gastrointestinal nematodes. The clinical efficacy was shown in two seasons, winter and spring, with predominance of different nematode populations. Groups of 15 calves were treated with RBZ alone, LEV alone and RBZ + LEV combination, and an untreated group was kept as a Control. RBZ and LEV plasma concentrations were quantified by HPLC. The clinical efficacy was determined by the faecal egg count reduction test. RBZ and LEV have similar plasma persistence, being detected in plasma over 24 hr post‐treatment. No PK interactions were observed after the combined treatment, with similar PK parameters ( p > .05) obtained for the single‐drug and the combination‐based strategy. In winter, the observed clinical efficacies were 96%, 99% and 100% for groups treated with RBZ, LEV and RBZ + LEV, respectively; however, in spring, the efficacies were 95%, 93% and 96% for the same groups. Remarkably, the combination was the only treatment that achieved 100% clinical efficacy against both Haemonchus spp and Ostertagia spp in winter; but the increased presence of Ostertagia spp. in spring (28% in untreated group) determined a tendency to reduced efficacies compared to winter time (only 10% of Ostertagia spp. in untreated group), even for the combined treatment. Overall, in a scenario where the nematode population is susceptible, the RBZ + LEV treatment may be a valid combination in cattle to delay the development of resistance, especially in winter when this combination achieved 100% of efficacy. Thus, selection of anthelmintic resistance will never occur. In fact, this is one of the greatest challenges for the whole cattle production system: to be one step ahead of anthelmintic resistance.